Increasing Entrepreneurial Intention with the Application of Experiential Learning Theory: An Innovative Learning Method and Empirical Test - Sukavejworakit, Krisakorn (Animo Repository, 2018)
Entrepreneurship is widely recognized by many scholars and the governments around the world as an essential driver of the economic prosperity. Over the past decades, entrepreneurship research has sought to understand the creation and execution of the entrepreneurial activity, with entrepreneurial intention becoming recognized as an excellent predictor of entrepreneurship activity and its subsequent consequences. As such, the researchers delved into how an entrepreneur’s intention is affected by their educational process, with the role of opportunity evaluation examined by the use of Experiential Learning Theory [ELT]. Liñán’s Entrepreneurial Intention [EI] Model was used to help with the evaluation of the study’s perceived desirability and perceived feasibility as the sources of entrepreneurial intention. From this process, an innovative learning method named ‘opportunity evaluation through experiential learning [OETEL]’ was developed and applied, from which it was hypothesized that OETEL would mediate perceived desirability, perceived feasibility, and entrepreneurial intention. This was subsequently followed by the participation of 160 Thai university students who participated in the OETEL experiment through their entrepreneurship activities. From the use of the SPSS PROCESS macro, results revealed that the OETEL process affected perceived desirability, perceived feasibility, and entrepreneurial intention significantly. Furthermore, the results revealed how the innovative learning application of experiential learning theory affects entrepreneurial intention. Practitioners can adapt this teaching method in entrepreneurial classrooms and policymakers can strategically encourage experiential learning in entrepreneurship education programs.